2005
DOI: 10.1111/j.1600-0501.2005.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of resonance frequency analysis for the determination of the primary stability of orthodontic palatal implants. A study in human cadavers

Abstract: This study shows that the short implant gives sufficient bone fixation, independently of placement. The quality of implantation and bone structure are more important than the length of the orthodontic implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 19 publications
6
49
0
9
Order By: Relevance
“…The implant stability is theoretically affected by the bone-implant contact (BIC) area, possibly owing to a larger amount of bone in contact with the implant producing a higher structure stiffness, resulting in higher interfacial strength. 17,18 Zhou et al 19 and Scarano et al 20 demonstrated that the BIC was correlated with the resonance frequency of the implant in animals and in retrieved human implants, respectively. In contrast, Ito et al 14 and Jun et al 21 indicated that there was no significant correlation between RFA measurements and BIC based on animal and human cadaver studies, respectively.…”
mentioning
confidence: 97%
“…The implant stability is theoretically affected by the bone-implant contact (BIC) area, possibly owing to a larger amount of bone in contact with the implant producing a higher structure stiffness, resulting in higher interfacial strength. 17,18 Zhou et al 19 and Scarano et al 20 demonstrated that the BIC was correlated with the resonance frequency of the implant in animals and in retrieved human implants, respectively. In contrast, Ito et al 14 and Jun et al 21 indicated that there was no significant correlation between RFA measurements and BIC based on animal and human cadaver studies, respectively.…”
mentioning
confidence: 97%
“…1,2 It is achieved by mechanical contact between the miniscrew surface and bone 3 and depends on the characteristics of devices 4,5 , insertion technique 4 and bone quality and quantity of the receptor site. 4,[6][7][8] The primary stability plays an important role in the successful secondary stability of miniscrews, since lack of immediate stability can lead to progressive mobility of the device and its subsequent loss.…”
Section: Introductionmentioning
confidence: 99%
“…Even though intraoral radiography is popular in clinics, it provides only low-resolution and two-dimensional images, which limits the visibility of the sites of interest. Histology and histomorphometric techniques can be used to examine the bone mineral quality and trabecular bone structure of grafted bone, but they can only provide one-time measurements that cannot be repeated on the same sample [23]. Nowadays, new imaging techniques such as cone beam computed tomography and micro-CT have made it possible to obtain high-resolution 3D images, and micro-CT has further provided the ability to directly analyze the bone architecture.…”
Section: Discussionmentioning
confidence: 98%